0627 The Effects of Insomnia Therapy on Depression, Anxiety, and Daily Functioning in Individuals with Insomnia and Mild Cognitive Impairment. (25th May 2022) - Morehouse, Allison; O'Hora, Kathleen; Hernandez, Beatriz; Lazzeroni, Laura; Zeitzer, Jamie; Friedman, Leah; Posner, Donn; Kushida, Clete; Yesavage, Jerome; Goldstein-Piekarski, Andrea
Abstract: Introduction: Insomnia is common in older adults with and without mild cognitive impairment (MCI), and is associated with worse neuropsychiatric symptoms (NPS) and impaired daily functioning. Evidence suggests treating insomnia may resolve some of these difficulties in cognitively normal adults. However, little is known about the effects of improving sleep on these domains in older adults with MCI. Methods: We examined whether MCI status moderates the improvements of a behavioral intervention for insomnia on NPS and daily functioning. 125 adults (mean age=69.18, 34.4% male) with insomnia (38 with MCI as determined by a Montreal Cognitive Assessment; MoCA score < 26) completed the Insomnia Severity Index (ISI), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and five domains (activity, vigilance, intimacy, productivity, and social) of the Functional Outcomes of Sleep Questionnaire (FOSQ) before (BL) and after (ETX) completing either the behavioral, cognitive, or combined components of Cognitive Behavioral Therapy for Insomnia (CBT-I). Linear mixed effects models were used to determine the effect of MCI status, time, and an MCI-by-time interaction on NPS and daily functioning while covarying for sex. Results: Treatment improved BDI (p<0.001), BAI (p<0.001), ISI (p<0.001), productivity (p<0.008), activity (p<0.001), social functioning (p=0.014), and FOSQ total score (p=0.015) regardless of MCI status at ETX compared to BL. Treatment did not significantly improve vigilance (p=0.154) or intimacy (p=0.439). There was a significant MCI-by-time interaction for the FOSQ social domain (p=0.041) with MCI participants showing greater improvements in social functioning compared to non-MCI participants. There were no other significant MCI-by-time interactions. Conclusion: These findings suggest insomnia therapy can similarly improve aspects of sleep-related daily functioning, insomnia severity, and NPS regardless of MCI. However, insomnia therapy may be more beneficial in improving social functioning for individuals with MCI. Support (If Any): NIMHR01MH101468-01; Mental Illness Research, Education, and Clinical Center (MIRECC) at the VAPAHCS